Salmonella as a Promising Curative Tool against Cancer - Ram Prasad Aganja; Chandran Sivasankar; Amal Senevirathne; John Hwa Lee (MDPI AG, 2022)
Bacteria-mediated cancer therapy has become a topic of interest under the broad umbrella of oncotherapy. Among many bacterial species, Salmonella remains at the forefront due to its ability to localize and proliferate inside tumor microenvironments and often suppress tumor growth. Salmonella Typhimurium is one of the most promising mediators, with engineering plasticity and cancer specificity. It can be used to deliver toxins that induce cell death in cancer cells specifically, and also as a cancer-specific instrument for immunotherapy by delivering tumor antigens and exposing the tumor environment to the host immune system. Salmonella can be used to deliver prodrug converting enzymes unambiguously against cancer. Though positive responses in Salmonella-mediated cancer treatments are still at a preliminary level, they have paved the way for developing combinatorial therapy with conventional chemotherapy, radiotherapy, and surgery, and can be used synergistically to combat multi-drug resistant and higher-stage cancers. With this background, Salmonella-mediated cancer therapy was approved for clinical trials by U.S. Food and Drug Administration, but the results were not satisfactory and more pre-clinical investigation is needed. This review summarizes the recent advancements in Salmonella-mediated oncotherapy in the fight against cancer. The present article emphasizes the demand for Salmonella mutants with high stringency toward cancer and with amenable elements of safety by virulence deletions.